2023
DOI: 10.1186/s13578-023-01062-y
|View full text |Cite
|
Sign up to set email alerts
|

ER Ca2+ overload activates the IRE1α signaling and promotes cell survival

Abstract: Background Maintaining homeostasis of Ca2+ stores in the endoplasmic reticulum (ER) is crucial for proper Ca2+ signaling and key cellular functions. Although Ca2+ depletion has been known to cause ER stress which in turn activates the unfolded protein response (UPR), how UPR sensors/transducers respond to excess Ca2+ when ER stores are overloaded remain largely unclear. Results Here, we report for the first time that overloading of ER Ca2+ can dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 103 publications
0
1
1
Order By: Relevance
“…Our research demonstrates that TMCO1 regulated the expression of CALR, and this impact is consistent with variations in intracellular calcium ion concentrations. It has been reported that TMCO1 and CALR control cell proliferation and death, respectively, in order to maintain calcium homeostasis in the endoplasmic reticulum [35]. However, our results showed that TMCO1 silencing also inhibited cell proliferation and cytoskeletal reorganization in addition to lowering CALR expression.…”
Section: Discussioncontrasting
confidence: 63%
“…Our research demonstrates that TMCO1 regulated the expression of CALR, and this impact is consistent with variations in intracellular calcium ion concentrations. It has been reported that TMCO1 and CALR control cell proliferation and death, respectively, in order to maintain calcium homeostasis in the endoplasmic reticulum [35]. However, our results showed that TMCO1 silencing also inhibited cell proliferation and cytoskeletal reorganization in addition to lowering CALR expression.…”
Section: Discussioncontrasting
confidence: 63%
“…Cells have a certain self-protection mechanism, and when calcium overload occurs in the ER, certain pathways are activated to maintain intracellular calcium homeostasis [47,48]. In addition, we also observed changes in intracellular calcium signal flow after inhibiting IP3R, L-type calcium pathway, and SERCA calcium pump.…”
Section: Discussionmentioning
confidence: 63%
“…Cells have a certain self-protection mechanism, and when a calcium overload occurs in the ER, certain pathways are activated to maintain the intracellular calcium homeostasis [48,49]. In addition, we observed changes in the intracellular calcium signal flow after inhibiting IP 3 R, the L-type calcium pathway, and the SERCA calcium pump.…”
Section: Discussionmentioning
confidence: 76%